Error estimate in the central limit theorem - Kasparavičiūtė, Aurelija; Padvelskis, Kazimieras (Lietuvos matematikos rinkinys, 2008)
In this paper, we determined, independent identically distributed random variable’s {Xk, k = 1,2,...} centered and normalized sum’s Sn = \sumn k=1 Xk distribution’s Fn(x) = P(Zn < x) exact error estimate in case of the normal approximation with one Cebyšova’s asymptotic expansion’s term.
Keywords: the Central limit theorem; normal distribution; error estimate; cumulants